2014
DOI: 10.1016/j.mce.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

In vivo production of novel vitamin D2 hydroxy-derivatives by human placentas, epidermal keratinocytes, Caco-2 colon cells and the adrenal gland

Abstract: We investigated the metabolism of vitamin D2 to hydroxyvitamin D2 metabolites ((OH)D2) by human placentas ex-utero, adrenal glands ex-vivo and cultured human epidermal keratinocytes and colonic Caco-2 cells, and identified 20(OH)D2, 17,20(OH)2D2, 1,20(OH)2D2, 25(OH)D2 and 1,25(OH)2D2 as products. Inhibition of product formation by 22R-hydroxycholesterol indicated involvement of CYP11A1 in 20- and 17-hydroxylation of vitamin D2, while use of ketoconazole indicated involvement of CYP27B1 in 1α-hydroxylation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 48 publications
(121 reference statements)
0
97
0
Order By: Relevance
“…The cyclodextrin served to hold the 20(OH)D3 substrate in solution and is often used for activity assays with low solubility substrates where it forms a hydrophobic cage around them, with a hydrophilic exterior (29,30). It could solubilize 200 μM 20(OH)D3, the maximum concentration used in this study (3,8,31). The incubation also contained a cofactor and regeneration system comprising 2 mM glucose-6-phosphate, 2 U/mL glucose-6-phosphate dehydrogenase and 500 μM NADPH.…”
Section: Methodsmentioning
confidence: 96%
“…The cyclodextrin served to hold the 20(OH)D3 substrate in solution and is often used for activity assays with low solubility substrates where it forms a hydrophobic cage around them, with a hydrophilic exterior (29,30). It could solubilize 200 μM 20(OH)D3, the maximum concentration used in this study (3,8,31). The incubation also contained a cofactor and regeneration system comprising 2 mM glucose-6-phosphate, 2 U/mL glucose-6-phosphate dehydrogenase and 500 μM NADPH.…”
Section: Methodsmentioning
confidence: 96%
“…We also demonstrated the ability of CYP11A1 to hydroxylate vitamin D3 at these positions and further showed that C23 is a major site of hydroxylation with 20,23-dihydroxyvitamin D3 being the next most abundant product after 20-hydroxyvitamin D3 (Slominski et al, 2005a; Tuckey et al, 2008a, 2008b, 2011). Importantly, we have provided initial evidence that CYP11A1-initiated metabolism of 7-DHC, vitamin D3 and vitamin D2 can occur under in vivo conditions (Slominski et al, 2009, 2012a, 2012b, 2014a, 2014b). The novel CYP11A1-derived hydroxy-derivatives of vitamin D3 are active in inhibiting proliferation and stimulating differentiation in a range of cell types cultured in vitro (reviewed in (Slominski et al, 2014a)), and in reducing inflammation and skin fibrosis in mice in vivo (Slominski et al, 2013, 2014a), but lack the toxic and calcemic effects seen with high doses of 1,25(OH) 2 D3 (Slominski et al, 2010; Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…The organs were collected using standard procedures (Slominski et al, 2014c). The incubations of adrenal fragments followed modifications of the protocols described previously (Slominski et al, 2009, 2014b). Briefly, after dissection from the adipose, the adrenals were cut with scissors into small fragments and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of 20(OH)D3, 22(OH)D3, 20,23(OH) 2 D3, 20,22(OH) 2 D3, 1,20(OH) 2 D3 also occurs in human dermal fibroblasts incubated with D3 substrate [71]. Similarly, production of 20(OH)D2, 17,20(OH) 2 D2 and 1,20(OH) 2 D2 was observed in human placentas ex-utero , adrenal glands ex-vivo , and isolated human epidermal keratinocytes and colorectal Caco-2 cells incubated with D2 [59]. …”
Section: New Pathways Of Vitamin D Activationmentioning
confidence: 99%